"Goodfellas". Aristocratic networks and institutionalized rule in Carthage during the 6th and 5th centuries BC - Fumadó Ortega, Iván (Gerión. Revista de Historia Antigua, 2013)
The Carthaginian Archaeology and History have been developed, in a more or less explicit way, under a colonial perspective. This can be noted even in the current university handbooks on the topic. Scholars have been more interested in the Carthaginian foreign affairs and its imperialism and colonialism than in the internal maturity of its institutions. This paper wants to offer a contextual classification of the written sources in order to read them again paying special attention to the political struggle between aristocratic networks as well as between them and the Carthaginian state institutions during the 6th and 5th centuries BC.
Keywords: Aristocratic networks; Carthaginian politics; Greek and Latin historiography.